andererseits - Yearbook of Transatlantic German Studies Vol. 9/10, 2020/21 - Donahue, William Collins; Mein, Georg; Parr, Rolf (andererseits - Yearbook of Transatlantic German Studies, 2021)
andererseits provides a forum for research, commentary, and creative work on topics related to the German-speaking world and the field of German Studies. Works presented in the publication come from a wide variety of genres including book reviews, poetry, essays, editorials, forum discussions, academic notes, lectures, and traditional peer-reviewed academic articles. In addition, we welcome contributions by journalists, librarians, archivists, and other commentators interested in German Studies broadly conceived. By publishing such a diverse array of material, we hope to demonstrate the extraordinary value of the humanities in general, and German Studies in particular, on a variety of intellectual and cultural levels. This issue features contributions by Leo A. Lensing, Norman M. Klein, Jens M. Gurr, and Julia Faisst.